Basic approach to poisoning focusing “Toxidrome” - Amin, Md Robed (Bangladesh Journal of Medicine, 2023)
Background: The term “toxidrome” is derived from the term “toxic syndrome.”A toxidrome is a constellation of signs and symptoms that are seen with particular classes of poisons. Methods: A systematic review of English literature was done with search item naming toxidrome and or basic approach to poisoning. Search engine was multiple leaded by pubmed having mesh term of toxidrome. The journal sites of asiajol and banglajol was also searched for related topics. Personal communication with toxicology related paper was also applied during the process. Results: All of the toxidromes can be identified using the a quick “toxicological physical exam.” No laboratory tests are necessary! The toxicologic physical exam focuses on the following components: Vital Signs, behavior like sleepy, normal, euphoric, agitated ? Pupils whether small, normal, big? Mucus membranes like checking the axillae whether it is dry, normal, wet?Bowel sounds to see whether it is decreased, normal, increased? There are 7 toxidromes that the emergency physician should be able to recognize and treat.These include: The anticholinergic toxidrome, cholinergic toxidrome, opioid toxidrome, opioid withdrawal toxidrome, sedative-hypnotic toxidrome, sedative-hypnotic withdrawal toxidrome, and sympathomimetic toxidrome. Beside these, two additional toxidrome has recently been introduced, one is serotonergic toxidrome and neuroleptic malignant toxidrome. Patients who take several substances may have a mixed toxidrome. For example, a patient who “speedballs” cocaine and heroin may have features of both the opioid and sympathomimetic toxidromes. Conclusion: Like all clinical syndromes, patients almost never exhibit every single feature of a particular toxidrome. When diagnosing a patient with a specific toxidrome you are looking for the one which best fits. Bangladesh J Medicine 2023; Vol. 34, No. 2(1) Supplement: 185-186